The shrubs in the forest: The use of woody species by 18th-century Labrador Inuit - Zutter, Cynthia (My University, 2012)
Despite low productivity rates and sparse tree cover in the circumpolar region, the Inuit identify woody plants and their products as important parts of their diet that provide essential nutrients and medicine. However, evidence of historic and prehistoric Inuit plant use is less well known. This article presents archaeobotanical research from two 18th-century Inuit sites in Northern Labrador. At both sites, abundant botanical remains were recovered, suggesting woody plants were consumed as food, used as medicines, and modified for many valuable purposes. These results are consistent with Inuit ethnobotanical studies, suggesting that woody plants contribute important elements to the Inuit economy today and have done so in the recent past.
Keywords: archaeobotany; Inuit; Labrador